PLACE AND ROLE OF ANCIENT CULTURES IN FORMATION AND DEVELOPMENT URBAN PLANNING OF FERGANA DURING BRONZE AND EARLY IRON AGES (Scientific journal of the Fergana State University, 2023)
This study is aimed at the basis of a critical analysis of a wide range of scientific literature highlighting the urbanization processes of Ferghana of the Bronze Age and Early Iron Age. The characteristic features of the development of urban culture for each period are presented separately. The problem of a peculiar solution by ancient architects of planning cities and settlements of the studied period is revealed.